Biocontrol potential of Bacillus subtilis CTXW 7-6-2 against kiwifruit soft rot pathogens revealed by whole-genome sequencing and biochemical characterisation - Chen, Tingting; Zhang, Zhuzhu; Li, Wenzhi; Chen, Jia; Chen, Xuetang; Wang, Bince; Ma, Jiling; Dai, Yunyun; Ding, Haixia; Wang, Weizhen; Long, Youhua (Frontiers in Microbiology, 2022)
Soft rot causes significant economic losses in the kiwifruit industry. This study isolated strain CTXW 7-6-2 from healthy kiwifruit tissue; this was a gram-positive bacterium that produced the red pigment pulcherrimin. The phylogenetic tree based on 16S ribosomal RNA, gyrA, rpoB, and purH gene sequences identified CTXW 7-6-2 as a strain of Bacillus subtilis. CTXW 7-6-2 inhibited hyphal growth of pathogenic fungi that cause kiwifruit soft rot, namely Botryosphaeria dothidea, Phomopsis sp., and Alternaria alternata, by 81.76%, 69.80%, and 32.03%, respectively. CTXW 7-6-2 caused the hyphal surface to become swollen and deformed. Volatile compounds produced by the strain inhibited the growth of A. alternata and Phomopsis sp. by 65.74% and 54.78%, respectively. Whole-genome sequencing revealed that CTXW 7-6-2 possessed a single circular chromosome of 4,221,676 bp that contained 4428 protein-coding genes, with a GC content of 43.41%. Gene functions were annotated using the NCBI non-redundant protein, Swiss-Prot, Kyoto Encyclopedia of Genes and Genomes, Clusters of Orthologous Groups of proteins, Gene Ontology, Pathogen–Host Interactions, Carbohydrate-Active enZYmes, and Rapid Annotations using Subsystem Technology databases, revealing non-ribosomal pathways associated with antifungal mechanisms, biofilm formation, chemotactic motility, volatile compound 3-hydroxy-2-butanone, cell wall-associated enzymes, and synthesis of various secondary metabolites. antiSMASH analysis predicted that CTXW 7-6-2 can produce the active substances bacillaene, bacillibactin, subtilosin A, bacilysin, and luminmide and has four gene clusters of unknown function. RT-PCR analysis verified that yvmC and cypX, key genes involved in the production of pulcherrimin, were highly expressed in CTXW 7-6-2. This study elucidates the mechanism by which B. subtilis strain CTXW 7-6-2 inhibits pathogenic fungi that cause kiwifruit soft rot, suggesting the benefit of further studying its antifungal active substances.